INFLAMMATION/INFECTION MANAGEMENT WITH TIMERS STEPS ON CLIENT DIABETIC FOOT ULCER - Bahri, Khairul; Hidayat, Rizki; Gitarja, Widasari Sri; Fajar, Kana (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Diabetic foot wounds are predisposed to infection. These infections are the result of microbial colonization of the wound surface. The development of such infections can also be influenced by factors such as the presence of dead tissue, excessive exudate, and bacterial colonization. Efforts to overcome wound inflammation/infection with inflammation/infection management using the TIMERS steps (Tissue management, Infection/Inflammation, Moisture balance, Epithelization advancement/edge, Repair and regeneration, social factors) involve care actors. The present case study aims to describe the management of inflammation/infection with the TIMERS Step in diabetic foot wound clients involving carers. The research design is a case study, carried out on three clients with diabetic foot wounds from blood sugar tests while meeting the criteria of diabetes mellitus, stage III and IV wounds with granulation, slough and signs of inflammation/infection treated with TIMERS Steps involving caregivers who are trained to identify care needs. The findings of this case study indicated that the management of inflammation and infection in diabetic foot wounds using TIMERS entails three distinct stages. These stages involve the cleansing of the wound with antiseptic fluids, the removal of necrotic tissue through mechanical and autolytic debridement, and the selection of antimicrobial dressings to prevent and treat wound inflammation and infection. The carer's comprehension of the nursing care process was deemed satisfactory. This case study concludes that management of inflammation/infection with the TIMERS step involves the carer in identifying factors that inhibit wound healing and can accelerate the improvement of skin/tissue integrity.